PEMBELAJARAN TEMATIK BAGI ANAK USIA DASAR(METODOLOGI DALAM ISLAM) - Muhammad Shaleh Assingkily; Uni Sahara Br. Barus (NIZHAMIYAH, 2019)
This article aims to study the concept of thematic learning as a methodology in Islam. The formulation of the problem in this study is how the concept of thematic learning as a methodology in Islam and why thematic learning is used as a learning concept for children of basic age. This study uses a qualitative approach with library research. The results of this study indicate that (1) the concept of thematic learning as a methodology in Islam is based on QS. 2: 129 and QS. 2: 151, namely the concept of visionary learning that integrates tilawah (skills), ta'lim (knowledge), and tazkiyah (attitude, character, integrity); and (2) Thematic learning is appropriate for elementary age children because; First, thematic learning is contextual and functional for children. Second, thematic learning derived from the concept of science in Islam (wahdah al-Ulum) or known as the integration of science, islamization of science, objectification of science, and interconnection of science. Third, integrated thematic learning in accordance with the direction to the development of talents, interests, and potential of students.